Factors influencing corporate taxpayers’ participation in special voluntary disclosure program / Haryanti Salleh Baihaki, Susan Hydra Sikayu and Amrizah Kamaluddin - Salleh Baihaki, Haryanti; Sikayu, Susan Hydra; Kamaluddin, Amrizah (Universiti Teknologi MARA Cawangan Sarawak, 2024)
This paper seeks to explore factors influencing corporate taxpayers’ participation in the Special Voluntary Disclosure Program (SVDP) 1.0. Semi-structured interviews were conducted with two corporate taxpayers, five tax agents and five tax officers. Purposive sampling was used in selecting the participants. Data were analysed using thematic analysis with NVivo 12. Five themes emerged as the main factors contributing towards corporate taxpayers’ participation in SVDP. The themes and subthemes were: (1) threat of punishment: tax penalty and the probability of tax audit; (2) procedural fairness: public assurance of the program and a simple procedure; (3) trust towards the tax authority: confidentiality of disclosed information and favourable treatment by tax officers; (4) tax awareness: awareness of SVDP and basic knowledge in tax laws and regulations; and (5) coping mechanism. The findings enrich the limited literature by offering a fresh perspective on non-financial determinants for partaking SVDP, which then serve as a guide to improve the attractiveness of similar programs in the future. An enhanced voluntary disclosure will benefit the tax authority as it saves time and cost of collecting information on tax audits and investigation cases.